The effect of enteral nutrition support on muscle function capacity and pulmonary functions in malnourished patients with Chronic Obstructive Pulmonary Disease - Degirmenci, Duygu; Şahin, Habibe; Soylu, Meltem (Progress in Nutrition, 2018)
Patients with Chronic Obstructive Pulmonary Disease (COPD) usually have a decreased muscle function capacity and pulmonary functions. The purpose of this study was to determine the effect of enteral nutrition support given in addition to diet on muscle function capacity, forced expiratory volume in second (FEV1) and tiffeneau index (FEV1/FVC) in malnourished patient with COPD. Forty patients with body mass indexes (BMI) below 18.5 kg/m2 were included in the study. Nutrition education was given to all patients then the patients were divided into two groups as treatment and control. Treatment group consumed two bottles of enteral nutrition product in addition to oral nutrition for three months. The muscle powers of the patients were measured with handgrip dynamometer and their FEV1 and FVC values were determined with pulmonary function tests, and tiffeneau indexes were calculated in the beginning and at the end of the study. In conclusion, enteral nutrition support increased hand grip strength and FEV1 without any significant effect on FEV1/FVC values in malnourished patients with COPD.